2012
DOI: 10.1007/s10545-012-9491-0
|View full text |Cite
|
Sign up to set email alerts
|

Maternal phenylketonuria: low phenylalaninemia might increase the risk of intra uterine growth retardation

Abstract: Hyperphenylalaninemia (HPA) is not the only risk factor for IUGR; PHE lower than 120 μmol/L could also be associated with the IUGR occurrence. Even if the monitoring of these pregnancies has been improved since the initiation of guidelines, we would like to stress on the importance of the dietary aspect of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 27 publications
0
32
2
1
Order By: Relevance
“…56 The incidence of intrauterine growth retardation is not increased if PHE control is achieved by 10 weeks gestation; however it increases with later onset of PHE control. 57 Additional attention should be paid to women with PAH deficiency who have themselves had poor PHE control throughout their lives. Lower maternal IQ, <85, is associated with later achievement of gestational PHE control and poorer fetal outcomes, although when optimal PHE control is achieved in mothers irrespective of their IQ, the fetal outcomes are improved.…”
Section: Clinical Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…56 The incidence of intrauterine growth retardation is not increased if PHE control is achieved by 10 weeks gestation; however it increases with later onset of PHE control. 57 Additional attention should be paid to women with PAH deficiency who have themselves had poor PHE control throughout their lives. Lower maternal IQ, <85, is associated with later achievement of gestational PHE control and poorer fetal outcomes, although when optimal PHE control is achieved in mothers irrespective of their IQ, the fetal outcomes are improved.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…58 Although studies have shown that PHE levels as low as 100 µmol/l are safe during gestation, there are concerns that persistently low maternal PHE levels, especially during the second and third trimesters, may be associated with an increased risk of IUGR. 57 The adverse effects of elevated PHE on the developing fetus warrant increased attention and intervention during gestation, with emphasis on preconception control as optimal. Women who become pregnant without appropriate PHE control will need significant support to attain PHE levels within the…”
Section: Clinical Featuresmentioning
confidence: 99%
“…With respect to the second issue, phenylalanine concentrations were both statistically and clinically significantly lower at T2 and T3 compared to T1, showing levels <30 mmol/L. This indeed is of clinical importance since too low phenylalanine concentrations in PKU are related to impaired growth and development (Rouse 1966;Smith et al 1990;Teissier et al 2012), and possibly also to physical and mental development in HT1 (de Laet et al 2011;van Vliet et al 2014). …”
Section: Day-to-day Variation Is Comparable For Phenylalanine and Tyrmentioning
confidence: 93%
“…This results in both high tyrosine and low phenylalanine concentrations (De Laet et al 2011;Daly et al 2012;Wilson et al 2000), with dietary treatment being primarily monitored based on tyrosine concentrations. In phenylketonuria, too strict dietary treatment, resulting in "low" phenylalanine concentrations, has shown to be related to impaired growth and development (Teissier et al 2012;Rouse 1966;Smith et al 1990;Pode-Shakked et al 2013). In tyrosinemia type II, high tyrosine concentrations are associated with mental retardation.…”
Section: Introductionmentioning
confidence: 99%